Arms and innovation entrepreneurship and alliances in the twenty-first-century defense industry - Hasik, James M. 1966- (University of Chicago Press, 2008)
With many of the most important new military systems of the past decade produced by small firms that won competitive government contracts, defense-industry consultant James Hasik argues in Arms and Innovation that small firms have a number of advantages relative to their bigger competitors. Such firms are marked by an entrepreneurial spirit and fewer bureaucratic obstacles, and thus can both be more responsive to changes in the environment and more strategic in their planning. This is demonstrated, Hasik shows, by such innovation in military technologies as those that protect troops from roads